Design and development of semiconductor courseware for undergraduate students. - Sihar, Suzaini; Abd. Aziz, Sidek; Sulaiman, Zainal Abidin (Asian Network for Scientific Information, 2011)
The aim of this study was to design and develop a computer courseware which serves as an e-book as a challenge towards e-learning application. The courseware entitled 'Fundamental of Semiconductor Devices' is intended to assist undergraduate-level student' learning by bringing a sense of reality to the concepts. The fast prototype design model is used to develop the courseware with the aid of the Macromedia Flash MX2004, Swift 3D, Adobe Photoshop development tools. The main purpose of this courseware is to overcome the student's misconception on several topics of semiconductor devices and to develop an e-book of Semiconductor Devices. Graphical animated presentations were designed to provide a solution to overcome misconception. Two pre-test and post-test were carried out, to monitor the student's performance before and after using the software. The sigma value at 95% confident intervals, reduce from 0.4 for the pre-test to 0.05 for the post-tests. The students' perception towards the courseware prototype is respectively positive and acceptable the mean score value exceeded 4.16 (SD = 0.76) for each items given. The results indicate that the prototype courseware offers students a real life understanding of the concept. The present study also showed that the students performed better and accept the multimedia software in their learning session, with sigma value <0.05 for post-test 1 and post-test 2. Using Likert scale (total mean of score = 4.16 and SD = 0.76) with Alpha Croanbach of 0.89 (>0.7) concluded that the courseware is acceptable.